Hawking Radiation of a Single-Partition Black Hole - Youngsub Yoon (Advances in High Energy Physics)
Brian Kong and the present author recently presented a new area spectrum and showed that the new area spectrum implies that the decay time of a single-partition black hole (i.e., a black hole with the area not big enough to have two or more partitions) is roughly constant. In this article, we show why the decay time of a single-partition black hole is roughly constant.